2018
DOI: 10.3892/etm.2018.6016
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin, a DPP4 inhibitor, alleviates diabetes‑associated cognitive deficits by decreasing the levels of apoptosis‑related proteins in the rat hippocampus

Abstract: Cognitive impairment is a prevalent but underestimated complication of diabetes, which can cause spatial memory and learning deficits. In the present study, a streptozotocin-induced type 2 diabetic rat model was employed to investigate the effects of vildagliptin, a new oral hypoglycemic agent that acts by inhibiting dipeptidyl peptidase-4, on diabetes-associated cognitive impairments, as well as the molecular mechanisms involved. The present findings demonstrated that vildagliptin treatment prevented memory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…Group III treated with Vilda (5 mg/kg/day; p.o. ; Novartis International AG, Switzerland) 1 h after 3NP injection [14]. Group IV treated with WM (15 μg/kg/day; i.v.…”
Section: Experimental Designmentioning
confidence: 99%
“…Group III treated with Vilda (5 mg/kg/day; p.o. ; Novartis International AG, Switzerland) 1 h after 3NP injection [14]. Group IV treated with WM (15 μg/kg/day; i.v.…”
Section: Experimental Designmentioning
confidence: 99%
“…Activated Akt coordinates intracellular signals and regulated several downstream targets of the cell death/survival pathways to inhibit apoptosis, including glycogen synthase kinase-3(GSK- 3) [ 45 ]. Akt phosphorylation regulates cell proliferation and promotes cell survival by subsequent inactivation of GSK-3β [ 20 ]. In the early step in the execution phase of cellular apoptosis, phosphorylated GSK-3 serves as an upstream regulator of programmed cell death to aggravate cell damage and increase caspase-3 activity, which is important in central nervous system diseases [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Akt/Glycogen synthase kinase 3β (Akt/GSK-3β) signaling pathway is critically involved in cell proliferation and apoptosis in many cell types, including hippocampal neurons [ 17 , 18 ]. The repressed Akt and stimulated GSK-3β have been proved to exacerbate neuronal damage in experimental intracerebral hemorrhage and diabetic encephalopathy [ 19 , 20 ]. There is compelling evidence that the PI3K-Akt pathway is the upstream signal pathway that negatively regulates the expression of GSK-3β [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A population‐based study showed patients using pioglitazone as an antidiabetic drug are at lower risk of developing dementia when compared with other drugs used to treat the same (Lu, Yang, Li, Hsieh, & Ou, ; Thabit & El, ). Also, DPP‐4 inhibitors like linagliptin and vildagliptin showed reduced memory impairment when used as a treatment approach in rats (Lietzau et al, ; Zhang et al, ). Moreover, probucol showed a decline in cognitive impairment in an insulin resistant mouse by protecting its blood–brain barrier (Mamo et al, ).…”
Section: Curing Diabetes Associated Alzheimer's Disease: a Long Way Tmentioning
confidence: 99%
“…inhibitors like linagliptin and vildagliptin showed reduced memory impairment when used as a treatment approach in rats (Lietzau et al, 2018;Zhang et al, 2018). Moreover, probucol showed a decline in cognitive impairment in an insulin resistant mouse by protecting its bloodbrain barrier (Mamo et al, 2018).…”
Section: Insulinmentioning
confidence: 99%